2008
DOI: 10.1002/lt.21419
|View full text |Cite
|
Sign up to set email alerts
|

Utility of liver allograft biopsy obtained at procurement

Abstract: Extended-donor criteria (EDC) liver allografts potentiate the role of procurement biopsy in organ utilization. To expedite allocation, histologic evaluation is routinely performed upon frozen-section (FS) specimens by local pathologists. This descriptive study compares FS reports by local pathologists with permanent-section (PS) evaluation by dedicated hepatopathologists, identifies histologic characteristics underrepresented by FS evaluation, and evaluates the efficacy of a biopsy decision analysis based on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 26 publications
3
36
0
1
Order By: Relevance
“…[30][31][32] This strategy is based on the rationale that healthier recipients could better tolerate a poor initial graft function or major postoperative complications. [33][34][35] Underlining this thesis, we have previously reported a series of 20 patients enjoying an excellent outcome despite the use of steatotic grafts, in great part related to the selection of recipients presenting with a low model for end-stage liver disease score.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] This strategy is based on the rationale that healthier recipients could better tolerate a poor initial graft function or major postoperative complications. [33][34][35] Underlining this thesis, we have previously reported a series of 20 patients enjoying an excellent outcome despite the use of steatotic grafts, in great part related to the selection of recipients presenting with a low model for end-stage liver disease score.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study confirmed that H&E-stained frozen biopsy overestimates MiS but underestimates MaS, when compared with permanent sections using more specific staining modality [23]. Therefore, it can be argued that a significant bias in most studies investigating fatty livers has been the use of only H&E-stained frozen biopsy specimens [13].…”
Section: Assessment Of Fatty Liver Graftsmentioning
confidence: 94%
“…It also appears to be preferable for cadaveric donors because it implies a substantial reduction of the cold ischemia time in comparison with routine histopathological processing. 7 The main limitation ascribed to the frozen-section procedure is represented by the risk of underestimating macrosteatosis while overestimating microsteatosis due to the presence of water droplets entrapped in hepato-cytes at the time of tissue freezing. Nonetheless, we recently reported that the frozen-section evaluation of pretransplant liver biopsies led to the successful utilization of livers from donors Ͼ 60 years old.…”
mentioning
confidence: 99%